The Carnivorous Saurischia in the Jura and Cretaceous Formations, principally in Europe - Huene, Friedrich von (1926)
The carnivorous Saurischia of the jurassic and cretaceous formations of North América are relatively well known by the many papers principally of Marsh, Osborn, Lambe, Gilmore, and others. All the more one misses the same for Europe, though many finds and descriptions are existing there even from an earlier time than in North América. But most of these specimens are much more fragmentary and incomplete, it being impossible to make such methodical excavations as the country is more cultivated.